Damage assessment of reinforced concrete structures using a model-based nonlinear approach – A comprehensive review. (20th December 2018) - Hanif, Muhammad Usman; Ibrahim, Zainah; Ghaedi, Khaled; Hashim, Huzaifa; Javanmardi, Ahad
Highlights: Review of developments in model-based damage detection methods in RC constructed systems. Uncertainties in the vibration-based methods considering linear systems. Incorporating nonlinear behavior in damage assessment methods. Developments in the constitutive modeling of concrete using CDPM approach. Proposed methodology for damage assessment that attempts to address the uncertainties by in linear models. Dependence on baseline data can be avoided in future developments (inverse problem). Abstract: Reinforced concrete construction is the most popular construction material so far and has significantly contributed to the constantly expanding infrastructure. Nonetheless, this material suffers from damage due to external loadings caused by temperature fluctuations, and dynamic and static loading. Many approaches have been investigated to detect, repair, and prevent such damage. Out of all the approaches, vibration-based damage detection approaches are the most popular approaches because of the easy acquisition of vibration characteristics and global information on structural conditions. However, these approaches have not been successfully implemented because of inadequacies in constitutive modeling, dynamic behavior modeling and various other constraints. This study presents a review with emphasis on concrete modeling that addresses the constraints in the vibration modeling by incorporating the nonlinear behavior. To serve this purpose, a damage assessment methodology is proposed which attempts to address constraints like model updating, sensitivity to damage, environmental influences and most importantly, eliminating the baseline data. The method has been briefly explained step-by-step by modeling an RC beam and validating it by laboratory testing. The contribution of this study is to review the latest developments on nonlinear model-based methods in the damage assessment of constructed systems, identify the constraints in field applications and attempt to address these issues by proposing a damage assessment methodology.